Initial factors affecting the clinical outcome after successful recanalization via MR-based mechanical thrombectomy in patients with acute ischemic stroke due to basilar artery occlusion. (14th September 2015) - Son, Seungnam; Kim, Yong-Won; Oh, Min Kyun; Kim, Soo-Kyoung; Park, Ki-Jong; Choi, Nack-Cheon; Kwon, Oh-Young; Lim, Byeong Hoon; Choi, Ho Cheol; Choi, Dae Seob
Abstract : Background and purpose: To determine the initial factors, including patient characteristics, stroke etiology and severity, time factors, and imaging findings, that could affect the clinical outcome of patients with acute ischemic stroke (AIS) caused by basilar artery occlusion (BAO) where successful recanalization was achieved via mechanical thrombectomy. Methods: Between March 2011 and December 2014, 35 patients with AIS caused by BAO received MRI/MR angiography-based mechanical thrombectomies, and recanalization was achieved with a Thrombolysis In Cerebral Infarction score of >2b. The patients were divided into a good outcome group (n=19), defined as those with a modified Rankin Scale (mRS) score of 0–2 at 3 months after stroke onset, and a poor outcome group (n=16), defined as a mRS score of 3–6. The differences between the groups were analyzed. Results: Initial National Institutes of Health Stroke Scale (NIHSS) score (good vs poor: 17.9±8.9 vs 27.6±8.5, p=0.003), posterior circulation Acute Stroke Prognosis Early CT Score (pc-ASPECTS) based on initial diffusion-weighted images (DWI) (good vs poor: 7.8±1.6 vs 5.4±1.8, p=0.001), pc-ASPECTS based on contrast staining on the post-thrombectomy control CT (good vs poor: 9.2±1.5 vs 6.3±2.2, p<0.001), and presence of contrast staining in the brainstem on that CT (good vs poor: 15.8% vs 81.6%, p<0.001) were significantly different between the groups. Conclusions: Patients with AIS caused by BAO with a lower initial NIHSS score, fewer lesions on initial DWI, and less contrast staining on the post-thrombectomy control CT have higher probabilities of a good clinical outcome after successful recanalization via a mechanical thrombectomy.